Changes in gut hormones and leptin in military personnel during operational deployment in Afghanistan. (22nd January 2015) - Hill, Neil E.; Fallowfield, Joanne L.; Delves, Simon K.; Ardley, Christian; Stacey, Michael; Ghatei, Mohammad; Bloom, Stephen R.; Frost, Gary; Brett, Stephen J.; Wilson, Duncan R.; Murphy, Kevin G.
<x xml:space="preserve">Abstract</x> Objective Understanding the mechanisms that drive weight loss in a lean population may elucidate systems that regulate normal energy homeostasis. This prospective study of British military volunteers investigated the effects of a 6‐month deployment to Afghanistan on energy balance and circulating concentrations of specific appetite‐regulating hormones. Methods Measurements were obtained twice in the UK (during the Pre‐deployment period) and once in Afghanistan, at Mid‐deployment. Body mass, body composition, food intake, and appetite‐regulatory hormones (leptin, active and total ghrelin, PYY, PP, GLP‐1) were measured. Results Repeated measures analysis of 105 volunteers showed body mass decreased by 4.9% ± 3.7% (P < 0.0001) during the first half of the deployment. Leptin concentrations were significantly correlated with percentage body fat at each time point. The reduction in percentage body fat between Pre‐deployment and Mid‐deployment was 8.6%, with a corresponding 48% decrease in mean circulating leptin. Pre‐deployment leptin and total and active ghrelin levels correlated with subsequent change in body mass; however. no changes were observed in the anorectic gut hormones GLP‐1, PP, or PYY. Conclusions These data suggest that changes in appetite‐regulating hormones in front line military personnel occur in response to, but do not drive, reductions in body mass.